Romantyczne zmagania z przeszłością - Junkiert, Maciej (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2024)
The book contains three selected articles by Kazimierz Brodziński, Jan Śniadecki and Maurycy Mochnacki, accompanied by critical commentaries and an introductory essay. The above mentioned played a key role in the so-called struggle between the Romantics and the Classicists. The publications of the former between 1818 and 1825 were linked to the birth of Romanticism in Polish literature and the departure from neo-classical aesthetics. The polemic was both generational and political, while the discussion of literary topics in the Polish press was subject to the rules of censorship, and concerned not only literary matters but also the question of whether Polish culture belonged to particular circles of European civilisation. The aim of this publication is to place the articles in the context of the artistic and historical disputes of the era, and to a lesser extent those that took place in the national arena, as this has already been outlined in detail. The focus will be, in the main, on contexts drawn from German language and culture. The starting point here is the relationship between Kazimierz Brodziński’s work and the critical output of Johann Gottfried Herder, followed by articles from Śniadecki and Mochnacki, as to how Herder and Brodziński praised or denied the rightfulness of drawing on and subsequently imitating foreign literatures.
The Romantics and Their Polemic with the Past